1983
DOI: 10.1111/j.1751-0813.1983.tb09583.x
|View full text |Cite
|
Sign up to set email alerts
|

Bovine abortion associated with Leptospira interrogans serovar hardjo infection

Abstract: During 1981, 265 bovine abortions were investigated by serological and histological methods for evidence of leptospiral infection. Leptospires were demonstrated in the tissues of 10 foetuses by a Levaditi silver impregnation technique. Serological testing of maternal sera indicated that Leptospira interrogans serovar hardjo was associated with 5 of the abortions while the remaining 5 were due to L. interrogans serovar pomona infection. In cases of abortion associated with L. interrogans serovar hardjo leptospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
3

Year Published

1988
1988
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 11 publications
0
5
0
3
Order By: Relevance
“…Similarmente, nos Estados da Bahia e São Paulo, esse sorovar foi apontado como o mais prevalente nas propriedades e nos animais (Castro et al, 2008;Oliveira et al, 2009), confirmando os achados clássicos em bovinos. Este sorovar, também relatado como prevalente em rebanhos bovinos de outros países, tem sido reconhecido como significante causa de falhas e alterações nos parâmetros reprodutivos (Higgins et al, 1980;Slee et al 1983;Tebrugge;Dreyer, 1985;Prescott et al, 1988;Ellis, 1994;Faine et al, 1999;Guitian et al 1999;Chiareli et al, 2012).…”
Section: Resultsunclassified
“…Similarmente, nos Estados da Bahia e São Paulo, esse sorovar foi apontado como o mais prevalente nas propriedades e nos animais (Castro et al, 2008;Oliveira et al, 2009), confirmando os achados clássicos em bovinos. Este sorovar, também relatado como prevalente em rebanhos bovinos de outros países, tem sido reconhecido como significante causa de falhas e alterações nos parâmetros reprodutivos (Higgins et al, 1980;Slee et al 1983;Tebrugge;Dreyer, 1985;Prescott et al, 1988;Ellis, 1994;Faine et al, 1999;Guitian et al 1999;Chiareli et al, 2012).…”
Section: Resultsunclassified
“…In addition, hardjo has been isolated from normal fetuses (191), the genital tracts of pregnant cattle (191), vaginal discharge after calving (193), and the genital tract and urinary tract of Ͼ50% of cows (197,198) and bulls (185). In Australia, both serovars hardjo and pomona were demonstrated in bovine abortions, but serological evidence suggested that the incidence of hardjo infection was much higher (182,305,529). In Scotland, 42% of cattle were seropositive for hardjo, representing 85% of all seropositive animals (187).…”
Section: Epidemiologymentioning
confidence: 99%
“…A total of 1122 serum samples were collected from cattle with the history of abortion, repeat breeding, jaundice and haemorrhagic mastitis (Table -2 Slee et al (1983) proved that serovar hardjo was associating with bovine abortions in Australia, whereas Thiermann (1982) reported that hardjo could produce mastitis and abortions. Sullivan and Callan (1970), Hoare and Claxton (1972), Gordon (1977) and Higgins et al (1980) reported association of clinical mastitis with hardjo in cattle.…”
Section: Resultsmentioning
confidence: 99%